High genetic differentiation of red gorgonian populations from the Atlantic Ocean and the Mediterranean Sea. Issue 8 (14th September 2017) - Pilczynska, Joanna; Cocito, Silvia; Boavida, Joana; Serrão, Ester A.; Queiroga, Henrique
ABSTRACT: Patterns of genetic variation within a species may be used to infer past events in the evolutionary history of marine species. In the present study we aimed to compare the genetic diversity of the red gorgonian Paramuricea clavata in the Atlantic Ocean and the Mediterranean Sea. For genetic markers we used microsatellites and a mitochondrial gene fragment. Our results revealed a distinct genetic composition and diversity between the Mediterranean and the Atlantic. The Mediterranean samples had higher microsatellite heterozygosity, allelic richness and private allelic richness. The hypotheses that can explain these patterns are the isolation of Atlantic populations and/or a founder effect. Additionally, a clear difference was obtained from the mitochondrial locus, since sequences from Atlantic and Mediterranean samples diverged by 1%, which is high for soft corals.